Writing imperial histories - Thompson, Andrew S. (Andrew Stuart), 1968- (Book collections on Project MUSE., 2013)
This book appraises the critical contribution of the Studies in Imperialism series to the writing of imperial histories as the series passes its 100th publication. The volume brings together some of the most distinguished scholars writing today to explore the major intellectual trends in Imperial history, with a particular focus on the cultural readings of empire that have flourished over the last generation. When the Studies in Imperialism series was founded, the discipline of Imperial history was at what was probably its lowest ebb. A quarter of a century on, there has been a tremendous broa.